The effectiveness of the Javanese Kickfun Game (J-KIG) as a medium for introducing Wayang Kulit to teenagers: The effectiveness of the Javanese Kickfun Game (J-KIG) as a medium for introducing Wayang Kulit to teenagers - Wibowo, Antonio Tri; Setyowati, Servatia Mayang; Saputro, Yulius Agung; Sulistiya, Febri; Sahrah, Alimatus (Jurnal Keolahragaan, 2025)
Wayang kulit is a Javanese cultural heritage that is full of moral and philosophical values, but adolescents' interest in it is decreasing. Therefore, an innovative approach is needed to reintroduce wayang kulit to the younger generation. This study aims to test the effectiveness of the Javanese Kickfun Game (J-KIG) in introducing puppetry to adolescents. The method used was a quasi-experiment with a one group pretest-posttest design. The research sample consisted of 14 adolescents from Pundong 1, Sleman, Indonesia. The instrument used was the J-KIG cognitive test, and the data analysis was carried out by the Wilcoxon Signed-Rank Test. The results of the normality test showed that the pretest data were normal and the posttest data were not distributed normally, so non-parametric analysis was used. The results of the Wilcoxon test showed a significant improvement between pretest and posttest scores (Z = −3.210; p = 0.001), with 13 respondents improving and 1 respondent having the same score. These findings show that J-KIG is effectively used as an educational medium to introduce the values of wayang kulit to adolescents. The implication of this study is that sports games combined with Wayang kulit, which is a Javanese cultural heritage rich in moral and philosophical values, can be an innovative strategy in physical education, character building, and cultural preservation.